Factors affecting adoption of electronic banking by bank customers in Dubai - Jasim, Aiysha Hameed (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
Despite the wide implementation of the e-banking system in developed countries, acceptance and adoption is still low in developing countries like United Arab Emirates (UAE). Moreover, there is also a shortage of empirical research on the implementation of the e-banking system among banks customers. The main objective of this study is to examine and investigate the Technology Acceptance Model (TAM) factors and Internet banking risks that influence on behaviour intention to adopt e-banking system by banks customers in Dubai. The research framework consists of eleven exogenous variables and one endogenous variable. The exogenous variables include TAM and Internet banking risks while the endogenous variable comprises behaviour intention to adopt the e-banking system. In addition, this study explains the extended TAM to be used in examining the factors of implementation of the e-banking system among customers in UAE. The sample of the present study consists of a total of 399 banks customers, analysed using Structural Equation Modelling (SEM) AMOS in order to examine causal relationships among the study's latent variables. The findings showed that the main hypotheses including perceived ease of use had a significant and positive effect on behaviour intention (BI) and usefulness of e-banking system adoption among customers in Dubai but ease of use had not significant effect on BI towards e-banking adoption. Additionally, Internet banking risks had a significant and negative influence on perceived usefulness and BI towards e-banking system. Moreover, perceived usefulness and ease of use are a good mediation between Internet banking risks and BI towards e-banking system. Finally, convenience had a significant and positive influence on BI towards e-banking adoption, but security and privacy had insignificant impact on BI. It can be concluded that the study provides significant insights into the state of e-banking usage among banks customers in UAE and provides points of reference for academics, practitioners and policy-makers by customers to adopt e-banking.